2005
DOI: 10.1021/jm0310986
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of the First Generation of Novel Potent, Selective, and in Vivo Active (Benzothiazol-2-yl)acetonitrile Inhibitors of the c-Jun N-Terminal Kinase

Abstract: Several lines of evidence support the hypothesis that c-Jun N-terminal kinase (JNKs) plays a critical role in a wide range of diseases including cell death (apoptosis)-related disorders (neurodegenerative diseases, brain, heart, and renal ischemia, epilepsy) and inflammatory disorders (multiple sclerosis, rheumatoid arthritis, inflammatory bowel diseases). Screening of our internal compound collection for inhibitors of JNK3 led to the identification of (benzothiazol-2-yl)acetonitrile derivatives as potent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 39 publications
0
105
1
Order By: Relevance
“…2 O-Q). We treated larvae between 48 and 58 hpf with two chemically distinct inhibitors of JNK, SP600125 (30) or AS601245 (31) and found that the active autophosphorylated form of JNK (30) was strongly reduced in larval extracts, as evidenced by immunodetection of the conserved diphosphorylated Thr-Pro-Tyr epitope of JNK ( Fig. 2 E and F) (32).…”
Section: Oriented Cell Division Does Not Contribute To Body Elongationmentioning
confidence: 99%
“…2 O-Q). We treated larvae between 48 and 58 hpf with two chemically distinct inhibitors of JNK, SP600125 (30) or AS601245 (31) and found that the active autophosphorylated form of JNK (30) was strongly reduced in larval extracts, as evidenced by immunodetection of the conserved diphosphorylated Thr-Pro-Tyr epitope of JNK ( Fig. 2 E and F) (32).…”
Section: Oriented Cell Division Does Not Contribute To Body Elongationmentioning
confidence: 99%
“…To further support the role of JNK in vincristine-mediated phosphorylation of Bcl-2 we examined the effects of several other commercially available inhibitors, including a second, structurally different, JNK-inhibitor (JNK inhibitor V; Gaillard et al, 2005), and an inactive structural analogue of SP6 (JNK inhibitor II; Bennett et al, 2001) that served a negative control for SP6. Although SP6 is the most commonly used inhibitor of the pathway, both it and JNK inhibitor V are ATP-competitive inhibitors that show a high degree of specificity towards the JNK1, 2, and 3 isoforms compared to a variety of other kinases (Bennet et al, 2001, Gaillard et al, 2005.…”
Section: Resultsmentioning
confidence: 99%
“…Although SP6 is the most commonly used inhibitor of the pathway, both it and JNK inhibitor V are ATP-competitive inhibitors that show a high degree of specificity towards the JNK1, 2, and 3 isoforms compared to a variety of other kinases (Bennet et al, 2001, Gaillard et al, 2005. In addition, we also examined the effect of inhibitors of the ERK and p38 pathways (U0126 and SB2, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For lead optimization, techniques such as hit evaluation [7], (Bio)isosteric replacements [18] and hit fragmentation [44] could be used. However, these techniques are beyond the scope of this review and will not be discussed further.…”
Section: Compound Optimizationmentioning
confidence: 99%